Real-Time Monitoring of Escherichia coli O157:H7 Adherence to Beef Carcass Surface Tissues with a Bioluminescent Reporter - Siragusa, Gregory R. (American Society for Microbiology, 1999)
A method for studying bacteria that are attached to carcass surfaces would eliminate the need for exogenous sampling and would facilitate understanding the interaction of potential human food-borne pathogens with food animal tissue surfaces. We describe such a method in which we used a bioluminescent reporter strain of Escherichia coli O157:H7 that was constructed by transformation with plasmid pCGLS1, an expression vector that contains a complete bacterial luciferase (lux) operon. Beef carcass surface tissues were inoculated with the bioluminescent strain, and adherent bacteria were visualized in real time by using a sensitive photon-counting camera to obtain in situ images. The reporter strain was found to luminesce from the tissue surfaces whether it was inoculated as a suspension in buffer or as a suspension in a bovine fecal slurry. With this method, areas of tissues inoculated with the reporter strain could be studied without obtaining, excising, homogenizing, and culturing multiple samples from the tissue surface. Use of the complete lux operon as the bioluminescent reporter eliminated the need to add exogenous substrate. This allowed detection and quantitation of bacterial inocula and rapid evaluation of adherence of a potential human pathogen to tissue surfaces. Following simple water rinses of inoculated carcass tissues, the attachment duration varied with different carcass surface types. On average, the percent retention of bioluminescent signal from the reporter strain was higher on lean fascia-covered tissue (54%) than on adipose fascia-covered tissue (18%) following water washing of the tissues. Bioluminescence and culture-derived viable bacterial counts were highly correlated (r(2) = 0.98). Real-time assessment of microbial attachment to this complex menstruum should facilitate evaluation of carcass decontamination procedures and mechanistic studies of microbial contamination of beef carcass tissues.